2020
DOI: 10.1186/s40337-020-0282-y
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and disordered eating behaviours in a community-based sample of Australian adolescents

Abstract: Background: People with diabetes have been shown to be at risk for disordered eating compared to their nondiabetic peers. However, the majority of studies have been conducted in relatively small samples drawn from clinical diabetes settings or registries. Community-based samples are required to better understand disordered eating behaviours in this population. In a large community-based population sample of Australian adolescents, this study aimed to (1) investigate disordered eating behaviours in adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…ON is problematic, but is also seen as a "salvation" from chronic diseases. Women with DM in particular tend to be more preoccupied with their diet and body weight, demonstrating a greater frequency and severity of EDs [13,57]. Weight status appears to be a strong predictor of EDs, especially among women with overweight/obesity attempting to lose weight [10,58].…”
Section: Characteristics Of Patients With Dm and On Tendenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…ON is problematic, but is also seen as a "salvation" from chronic diseases. Women with DM in particular tend to be more preoccupied with their diet and body weight, demonstrating a greater frequency and severity of EDs [13,57]. Weight status appears to be a strong predictor of EDs, especially among women with overweight/obesity attempting to lose weight [10,58].…”
Section: Characteristics Of Patients With Dm and On Tendenciesmentioning
confidence: 99%
“…It was first described by Bratman [2] as an exaggerated, unhealthy obsession with healthy eating. The difference Nutrients 2021, 13,3823 2 of 14 between adhering to healthy eating principles versus ON is that, in the latter case, the affected individual might be driven by dietary asceticism, cherry-picked evidence, or even by evidence-based recommendations, leading to a restrictive dietary pattern in pursuit of improved health [3]. Moreover, ON often has an underlying psychopathology, with a frequent overlap of symptoms between ON and anorexia nervosa (AN), obsessivecompulsive disorder (OCD), somatic symptom disorder, illness anxiety disorder, and psychotic spectrum disorders [4], leading to the development of ON as a manifestation of "healthism" [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eating disorders and disordered eating are more common in individuals with diabetes compared to the general population. In one recent study (Pursey et al, 2020) which surveyed secondary school students, disordered eating behaviours were considerably more common in individuals with diabetes (13.5%) compared to without diabetes (4.7%), though the authors did not distinguish between type 1 and type 2 diabetes. It is worth noting that while type 1 diabetes (an autoimmune condition leading to lack of insulin production) has historically been far more common in paediatric patients, the prevalence of type 2 diabetes (associated with modifiable lifestyle factors as well as genetic factors, and leading to insulin resistance rather than lack of production) is steadily increasing (Botero & Wolfsdorf, 2005).…”
Section: Eating Disorders In Paediatric Diabetesmentioning
confidence: 94%
“…However, the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM-V) (American Psychiatric Association, 2013) classifies insulin omission as a purging behaviour that can be associated with a diagnosis of Bulimia Nervosa when present alongside binge eating, or Anorexia Nervosa if the person is severely restricting both food and insulin. A recent large scale study found 17% of young people questioned reported insulin restriction (Pursey et al, 2020) whilst other studies suggest that up to 40% of young people with T1D have used insulin manipulation for weight loss (Pinhas-Hamiel et al, 2015). This behaviour is a particular concern for those caring for young people with T1D due to the significant negative impact it can have on health and increased mortality rates (Peveler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%